2015
DOI: 10.15640/jaes.v4n1a3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of New Crop Residues on Recovery of 15n Previously Added Residues by Maize

Abstract: A research was conducted to evaluate the effect of addition of new crop residues on recovery N at two crop cycle by maize. Two crops residue (rice straw=RS and soybean=SY) were grown in a glass-house under four 15 N concentration, i.e, 0 mM (N0), 0.625 0 mM (N1), 2.5 0 mM (N2), and 10 mM (N3) supplied as CO( 15 NH2)2, in plastic pots containing 5 kg of quartz sand. The maize as plant pots containing 10 kg of soil and placed in the glasshouse, it was conducted to evaluate the microbial biomass N and recovery N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This C3 treatment (50% peanuts + 50% rice straw) showed the best synchronization between the release of nutrients and the need for plants to meet nutrient needs, starting from the vegetative phase until before harvest, with an NUE value of 42.21%. Sholihah and Sugianto (2015) reported that mixing rice straw and green manure derived from legume residues may improve the synchronization between N release and demand, thereby contributing to increased yields and reduced N losses from soil-crop systems.…”
Section: Discussionmentioning
confidence: 99%
“…This C3 treatment (50% peanuts + 50% rice straw) showed the best synchronization between the release of nutrients and the need for plants to meet nutrient needs, starting from the vegetative phase until before harvest, with an NUE value of 42.21%. Sholihah and Sugianto (2015) reported that mixing rice straw and green manure derived from legume residues may improve the synchronization between N release and demand, thereby contributing to increased yields and reduced N losses from soil-crop systems.…”
Section: Discussionmentioning
confidence: 99%